Occlusal plane flattening by miniscrew in skeletal open bite:a case report - Ahmad Sodagar; Farhad Sobouti; Negin Shahsavari (Babol University of Medical Sciences, 2014)
Introduction: Different factors such as respiratory disorders , genetics, facial growth pattern , tongue malfunction and malposition are associated with anterior open bite. Skeletal open bite is often appeared by increased posterior dentoalveolar height of maxilla and backward rotation of mandible. Many treatment approaches have been developed for treatment of increased facial height problems. Achieving absolute anchorage has been a very efficient device for intrusion of posterior segments. In this article, the treatment of patient with severe skeletal open bite and facial imbalances was explained .researchers of the present study used mini screws for leveling of upper arch by intrusion of premolars .Then, appropriate orthognathic surgery was done.